Truth as Presence (Iter, 2022)
The lesson is structured around the human truth that expressed in wordsand implies an active relationship between subjects communicating amongthemselves, and also with that are shown and, somehow, request to be known.A ristotel ian-Thom is tic theory States that, in order to have true knowledge, therelationship o f the knower with what is known musí result in a conversión,adaptation or assimilation, o f one into the other. Despite its being in highdisrepute today, this is still the mandatory starting point fo r every reflectionon the subject.Human truth is always relative and not absolute, and it is sometimesjoined to lies or errors. The compass settling the truth-lie divergence andsuggesting the convenience o f choosing one or the other is righteousness.Acting well and conscientiously, guarantees that we are true.
Keywords: Truth, communication, relationship, adaptation, language, lies